The Effectiveness of AMF Inoculum to Enhance The Potency of Papuan Crandallite Phosphate Rock and The Growth of Cocoa Seedling - Suparno, Antonius (JOURNAL OF TROPICAL SOILS, 2009)
Phosphate rock fertilizer has slow solubility; therefore, it is suitable and more effective to be applied on annual crop plantation. To increase the solubility and the effectiveness of phosphate rock application, inoculation of the Arbuscular Mycorrhyzal Fungi (AMF) is required. Experiments were conducted at the Cikabayan Farm, Bogor Agriculture Institute, West Java. The objective was to study the effectiveness of AMF inoculation in increasing the potency of Papuan Crandallite Phosphate Rock to the growth of cocoa seedlings.  A factorial experiment was set up in a complete randomized design. The first factor was AMF inoculation, consisting of none AMF, Manokwari indigenous AMF and Mycofer AMF, and the second factor was five dosages of the Papuan Crandallite Phosphate Rock (PCPR), consisting of  0,  0.5,  1.0,  1.5 and 2.0 g P2O5 / seedling. The dosage of 2.0 g P2O5 SP-36 per seedling was used as a comparison. Cocoa seeds of F-1 Upper Amazon Hybrid (UAH) were collected from the Coffee and Cacao Research Center, Jember, East Java. The seedlings were grown in polybags of 20 cm x 30 cm size, with ultisol acid soil obtained from Jasinga (West Java) as the growing medium under 60% of shading net for four months. The media contained 17.03 cmol kg-1 of exchangeable Al.  The results showed that increasing the dosages of PCPR at the AMF inoculated seedlings resulted to the linear increase of shoot dry weight and P uptake by 50.14% and 64.88%, respectively; and this was lower than the inoculation of Manokwari indigenous AMF which increased shoot dry-weight by 66.30% and P uptake by 65.45%. Whereas the shoot dry-weight and P uptake of the non-mycorrhizal seedlings increased by 73.56% and 121.94%, respectively. Mycofer inoculants were found to be much more effective in increasing the shoot dry-weight by 127.55% and P uptake by 45.16% than that of the Manokwari indigenous AMF, which increased by 95.97% and 21.29% in shoot dry-weight and P uptake, respectively at the PCPR dosage of 2.0 g P2O5 / seedling as compared to the non-inoculated seedlings.